Improving students' writing skills using storyboard - Rahmadina, Cut Anandea; Susilawati, Endang; Rezeki, Yanti Sri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
In English language learning, writing is a skill that allows students to express their ideas, opinions, and thoughts effectively. However, students at SMPN 03 Entikong demonstrated low writing proficiency. This research aimed to investigate how the implementation of the Storyboard in teaching solves students’ writing problems. Storyboard is a teaching tool that displays a sequence of pictures accompanied by the appropriate words and sentences to describe events in the story. This research was conducted through classroom action research, which was carried out in two cycles with 36 students in Grade VIII-B as participants. Data were collected using writing test, observation checklist, and field notes. The quantitative findings showed an improvement in the average of the writing test score from 63.44 to 72.22. The qualitative results indicated that the implementation of Storyboard in the writing instruction and practice helped students to express ideas clearly, choose appropriate vocabulary, and use correct grammar in their writing, especially for the narrative text. Thus, it can be concluded that Storyboard improved students’ writing skills.